Competency and Professional Development of Islamic Religious Education Teachers: Kompetensi dan Pengembangan Profesional Guru Pendidikan Agama Islam - Zakiya Very Ayu Suryatina; Sugeng Solehuddin; Sopiah Sopiah; Abdul Khobir; Asnalia Rokhmah (Academia Open, 2027)
General Background Teacher professionalism is central to educational quality, while digital transformation requires Islamic Religious Education teachers to combine pedagogical competence with technological adaptability and moral-spiritual responsibility. Specific Background Contemporary PAI teachers face rapid digitalization, changing social conditions, administrative burdens, unequal digital literacy, and limited access to professional training. Knowledge Gap Previous studies remain fragmented, commonly examining pedagogical or professional competence separately and providing limited integration of continuous professional development, digital literacy, Islamic values, and Society 5.0 demands within a comprehensive framework. Aims This qualitative study examines the current development of PAI teacher competence and professionalism, the factors shaping that development, and adaptive strategies relevant to contemporary education through observations, in-depth interviews, and documentation involving teachers, principals, and students. Results Four central dimensions emerged: strengthened pedagogical competence, improved digital competence, cultivation of spirituality and exemplary character, and active participation in professional learning communities and continuous professional development. Barriers included restricted training access, administrative workload, and differences in computer literacy. Novelty The study frames PAI teacher professionalism as an integrated multidimensional process combining pedagogical, professional, social, spiritual, and digital competencies. Implications Educational institutions and government agencies should provide systematic, equitable, and sustained support for digital professional development, academic culture, professional learning communities, spiritual development, and context-responsive training. Highlights: Pedagogical capability, technology literacy, spiritual exemplarity, plus continuous learning formed four central dimensions. Restricted training access, administrative workload, plus uneven computer literacy remained primary barriers. Student-centered instruction, project-based learning, authentic assessment, plus online media reflected a transformative paradigm. Keywords: Islamic Religious Education, Teachers, Competency Development.